Requirements for the content of harmful substances in market products of plastics and rubber. Part III. Electrical and electronic equipment, batteries and accumulators - Kolasa, Dorota; Lach , Jakub; Wróbel, Kamil; Samsonowska, Katarzyna; Kaszuba, Alicja; Stępkowska, Aneta; Wróbel , Justyna (Polimery, 2023)
The article is a continuation of the existing legal acts review on the safety of products placed on the European Union market. The review, in part III concerning the provisions on the control of harmful substances in electrical and electronic equipment as well as batteries and accumulators, covers both EU legal acts and national acts transposing EU regulations into Polish law in this regard.